Engineering cleavage efficient 2A peptides for enhancing monoclonal antibody expression in CHO cells - Siah, Kok Kian (2015)
2A peptides are derived from various picorna viruses and are used to encode proteins in a single open-reading-frame (ORF). The polyprotein that is produced by the virus is cleaved co-translationally, through a “ribosomal-skipping” mechanism. 2A linked genes have been used in studies to co-express multiple genes in a single vector, producing equal amounts of product. Expressing heavy chain (HC) and light chain (LC) genes in a single transcript using 2A peptide helps to produce equal amounts of each genes, thereby reducing the formation of aggregates and non-expressing clones. In our study, a series of vectors were engineered by modifying 2A peptide sequence, linkers and furin recognition sites to enhance monoclonal antibody (mAb) trastuzumab expression in Chinese Hamster Ovary (CHO) cells. Membrane anchors were also incorporated to remove incorrectly processed mAb. While no vectors had improved mAb expression compared to control, FPTM, a vector with the membrane anchor derived from Human platelet-derived growth factor receptor transmembrane domain (PTM), had the highest expression level (80%) of the control. Western blot analysis of FPTM also showed improved mAb quality as compared to control without membrane anchor. Our findings also identified other potential vectors which could be screened further for their cleavage efficiency.